2009
DOI: 10.1179/174329408x315616
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectrical properties of PET spunbonded nonwovens deposited with ITO thin films by RF sputter coating

Abstract: Indium tin oxide (ITO) films were deposited on polyethylene terephthalate (PET) spunbonded nonwovens using radio frequency (RF) magnetron sputtering under different conditions. Indium tin oxide films with different thicknesses between 56 and 224 nm showed varying transmittances in the visible and ultraviolet regions. The transmittance of the nonwoven decreased as the thickness of the ITO film increased. The electrical properties of the material were also affected by the sputtering conditions. Lager sputtering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The sheet resistance values at room temperature were achieved using the standard four-point probe method. If the film thickness d is uniform, the electrical resistivity ρ can then be determined using the relation 19,20…”
Section: Methodsmentioning
confidence: 99%
“…The sheet resistance values at room temperature were achieved using the standard four-point probe method. If the film thickness d is uniform, the electrical resistivity ρ can then be determined using the relation 19,20…”
Section: Methodsmentioning
confidence: 99%
“…7 Hence, thin film materials based on Ta and Mo metals have been used for a wide variety of engineering applications such as under layers in magnetic recording media and high temperature protective coatings. 8 For instance, Ta-Mo is the basis of a family of oxidation and corrosion resistant coatings that have been used on Ni based and Ta based superalloys. 7 However, the high temperature oxidation behaviour of nanostructured Ta-Mo coatings on Ni based super alloy substrate is scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ta–Mo is the basis of a family of oxidation and corrosion resistant coatings that have been used on Ni based and Ta based superalloys 7. However, the high temperature oxidation behaviour of nanostructured Ta–Mo coatings on Ni based super alloy substrate is scarce in the literature 9…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have focused on the effect of surface treatment and coating thickness on film properties in recent years. Wang et al studied the optoelectrical properties of PET spunbonded non-wovens deposited with ITO thin films by RF sputter coating 8. They found that indium tin oxide films with different thicknesses between 56 and 224 nm showed varying transmittances in the visible and ultraviolet regions and the transmittance of the non-woven decreased as the thickness of the ITO film increased.…”
Section: Introductionmentioning
confidence: 99%